The Pushcart prize XIV. - Henderson, Bill 1941-
A yearly anthology of fiction, essays and poetry from the small presses chosen by writers. Included are Susan Onthank Mates' Theng, on refugees from Indochina, Joseph Novakovich's Honey in the Carcase, on the war in Yugoslavia, and Charles D'Ambrosio's Jacinta, on rural Oregon.